2021
DOI: 10.1038/s41598-021-87380-y
|View full text |Cite
|
Sign up to set email alerts
|

Collagen molecular phenotypic switch between non-neoplastic and neoplastic canine mammary tissues

Abstract: In spite of major advances over the past several decades in diagnosis and treatment, breast cancer remains a global cause of morbidity and premature death for both human and veterinary patients. Due to multiple shared clinicopathological features, dogs provide an excellent model of human breast cancer, thus, a comparative oncology approach may advance our understanding of breast cancer biology and improve patient outcomes. Despite an increasing awareness of the critical role of fibrillar collagens in breast ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 99 publications
(72 reference statements)
0
11
0
Order By: Relevance
“…Since the total number of aldehydes involved in cross-linking is only ~ 8% lower in KO collagen compared to the control, the data implies that the Hyl ald -derived cross-linking is critical to confer insolubility on type I collagen. This is likely the reason why collagen enriched in the Hyl ald -derived cross-links accumulates without being readily degraded by proteolytic enzymes in fibrosis 28 , 56 , 57 and also in desmoplastic tumors such as pancreatic ductal adenocarcinoma 58 , lung cancer 29 , breast cancer 31 , 59 and oral cancer 30 . Such stiffened collagen matrix may not only form a shelter for cancer cells to protect them from immune cells and anti-cancer drugs but also serve as a means for cancer cells to attach, migrate and metastasize efficiently 41 , 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the total number of aldehydes involved in cross-linking is only ~ 8% lower in KO collagen compared to the control, the data implies that the Hyl ald -derived cross-linking is critical to confer insolubility on type I collagen. This is likely the reason why collagen enriched in the Hyl ald -derived cross-links accumulates without being readily degraded by proteolytic enzymes in fibrosis 28 , 56 , 57 and also in desmoplastic tumors such as pancreatic ductal adenocarcinoma 58 , lung cancer 29 , breast cancer 31 , 59 and oral cancer 30 . Such stiffened collagen matrix may not only form a shelter for cancer cells to protect them from immune cells and anti-cancer drugs but also serve as a means for cancer cells to attach, migrate and metastasize efficiently 41 , 60 , 61 .…”
Section: Discussionmentioning
confidence: 99%
“…29,31 Some of these studies indicated that higher levels of LH2 and consequent cross-linking are correlated with advanced stages and metastasis of cancer. 29,30 When LH2 expression is suppressed in cells that overexpress LH2, the metastatic propensity appears to be blunted in animal/cell models. 28,31 In the last decade, multiple studies have focused on the role of LH2 in cancer.…”
Section: Lysyl Hydroxylase 2: a Key Enzyme For Collagen Stability And...mentioning
confidence: 99%
“…26,27 In fact, recent studies have indicated that abnormal collagen cross-linking is associated with cancer growth and metastasis. [28][29][30][31][32] In this review, we provide a biochemical/molecular overview of collagen cross-linking, its role in OSCCs and possible clinical implications.…”
mentioning
confidence: 99%
“…Despite the significant progress in diagnostics and treatment that has been achieved over the recent several decades, mammary gland tumours remain the global cause of early death of people and veterinary patients (Mysak et al, 2018;Terajima et al, 2021). Comparative studies of the mammary gland tumours in dogs, which were conducted in different countries, should take into account possible change in the prediction due to different shares of sterilized females among the general population of dogs (Peña et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In samples of malignant tumours of the mammary gland, lysine residuals, especially telopeptides, are significantly more hydroxiled compared with non-tumour tissues of the mammary gland. Such changes promote increase in mediated transversal binding of collagen in the conditions of neoplasias in the mammary gland, which may cause metastasis of cancer cells in such patients (Terajima et al, 2021). In different histological types of tumours of the mammary gland in canines, there were observed different patterns of collagen fibers: fibers in tubular carcinoma were located mainly around its parenchyma, while in solid tumour, they were across the entire parenchyma and around each tumour cell (Borghesi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%